WORKPLACE VIOLENCE TOWARDS NURSES OF INTENSIVE CARE AREAS AND EMERGENCIES AT CIVIL HOSPITAL KARACHI - Khadim Hussain Maaari; Chaudhry Muhammad Amjad; Muhammad Ibrahim Ansari (Journal of University Medical & Dental College, 2017)
ABSTRACT: INTRODUCTION: Workplace violence (WPV) is very common routine problem faced by majority of health care providers among them nurses are at great risk of violence because of nature of their work and usual contacts with patients and their relatives. Most of the cases are not handled and reported properly and these incidents include verbal abuse, physical assault, bullying/mobbing, and sexual harassment. OBJECTIVES: To determine the prevalence of Workplace violence being faced by nurses at work and To ﬁnd out the nature of workplace violence among nurses. METHODOLOGY: A cross sectional survey was conducted and questionnaire was adapted from a standardized questionnaire designed collaboratively in GENEVA (2003) by the International Labor Oﬃce (ILO), the International Health Organization (IHO), the International Council of Nurses (ICN), and the Public Services International (PSI). RESULTS: Out of 104 questionnaire Ninety nurses responded to questionnaire (response rate was 86.5%). The prevalncey of WPV was 35.5% and respondents reported that exposure to physical attacks (46.7%), verbal abuse (52.2%), bullying/mobbing (27.8%) and sexual harassment (15.6%) at least one time during their last year of service. Most of the violence was attempted by patients and their family members and majority of sexual harassment cases were reported by female nurses and most of them were attempted by staﬀ or co-workers. CONCLUSION: High rate of workplace violence shows that the environment in which nurses are working is not safe and healthy for them and preventive measures are needed to protect the nurses at their work place.